Dayanita Singh: Let's See (Gottingen; Steidl, 2022)
A photo-novel of Dayanita Singh$1 (Bs earliest years as a photographer A return to a time when Dayanita Singh (born 1961) did not yet consider herself a photographer, Let$1 (Bs See is the probing remembrance of (3z(Ban eye I no longer have access to.(3y (BSingh has recently poured through 40 years of her archive$1 (B80% of which remains unseen$1 (Bexploring scans of her contact sheets and being amazed by the gentle and tender images from the 1980s and $1 (B90s she had since forgotten$1 (Bhostel roommates, friends with whom she lived, family, weddings, funerals; portraits of herself and those who would become important characters in her life: her mother, Nony Singh, the musician, Zakir Hussain, and Mona Ahmed, whom she depicted in the emotive visual biography Myself Mona Ahmed (2001).s
English
Keywords: TR624-835 Technology- Applied Photography